THE VIOLATION OF IMMUNITY AND DIPLOMATIC RIGHTS: A STUDY OF INDONESIAN EMBASSY WIRETAPPING CASE IN MYANMAR 2003-2004 IN THE ASEAN COMMUNITY SECURITY RESISTANCE BASED ON THE 1961 VIENNA CONVENTION - Theacornelia, Christella Jessicha; Latifah, Emmy (Journal of ASEAN Dynamics and Beyond, 2022)
Immunity rights and diplomatic immunity are guaranteed protection of the rights granted by the international community legally through a collective agreement in the 1961 Vienna Convention to the diplomatic representatives to be able to perform their duties properly. The guarantee rights are in the form of the right to do their activities, the right from immunity to regulation regarding assets acquired, including the place of the embassy building. Wiretapping is an effort or attempt to legally invade the private space of another party. At the state level, wiretapping can be used as a threat for security issues. In this study, the author tried to describe the case of wiretapping the Indonesian Embassy in Myanmar in 2004. Besides explaining through the Vienna Convention perspective, as Myanmar and Indonesia are ASEAN Member Countries, the author will try to reveal ASEAN role mainly in ASEAN Security Community project.